187k views
0 votes
1/2 (5-2h) = h/2, solve for h

1/2 (5-2h) = h/2, solve for h-example-1

2 Answers

5 votes

Answer:

h = 1 2/3

Explanation:

1/2 (5-2h) = h/2

Multiply each side by 2

(5-2h) = h

Add 2h to each side

(5-2h +2h) = h+2h

5 = 3h

Divide by 3

5/3 = 3h/3

5/3 =h

1 2/3 = h

Check

1/2 (5-2*5/3) = 5/3/2

1/2 ( 5 - 10/3) = 5/6

1/2 ( 15/3 - 10/3) = 5/6

1/2 ( 5/3) = 5/6

5/6 = 5/6

User Yeraycaballero
by
6.1k points
3 votes

Answer:

A

Explanation:

So we have the equation:


(1)/(2)(5-2h)=(h)/(2)

First, let's multiply both sides by 2 to get rid of the fractions. The 2s will cancel. So:


2((1)/(2)(5-2h))=2((h)/(2))

Simplify:


5-2h=h

Add 2h to both sides:


5=3h

Divide both sides by 3:


h=5/3

Change into mixed fractions:


h=1(2)/(3)

So, our answer is A.

And we're done!

To check, substitute 5/3 back in:


(1)/(2)(5-2(5/3))=((5/3))/(2)

Multiply and divide:


(1)/(2)(5-10/3)=(5)/(6)

Subtract on the left:


(1)/(2)(5/3)=(5)/(6)

Multiply:


(5)/(6)\stackrel{\checkmark}{=}(5)/(6)

So, our answer is correct!

User Eng Cy
by
6.3k points